PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA KANTOR CAMAT AMUNTAI TENGAHKABUPATEN HULU SUNGAI UTARA - Syahrusiani, Hj.; Hendrayani, Hendrayani; Sarnubi, Muhammad Said (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Services at the Central Amuntai Sub-District Office, have not been maximized in providing a service, namely the lack of attention and ability of employees in the form of providing information to visitors, so that misunderstandings often occur, services are less precise, and lack of socialization / direction. Research Objectives to find out the influence and magnitude between service quality on community satisfaction. The research method used is Quantitative with associative type cause and effect and explains systematically. The data collection techniques used are observation, questionnaires and documentation. Data sources were taken using the Slovin formula with simple random sampling techniques totaling 75 respondents. The results showed that the results of the Service Quality variable (X) had a significant effect on the Community Satisfaction variable (Y) at the Central Amuntai Sub-District Office, HSU Regency. This can be seen from the level of satisfaction as evidenced by the simple linear regression analysis Y = 22.294 + 0.089 X, which means that every one increase in Service Quality has an effect of 0.089 on Community Satisfaction, so there is an influence between variable X on variable Y. Meanwhile, from the results of the t test calculation, namely the tcount of 2, 438 compared to the t table (db = 73) which is 2, 379 with a significant level of 0.01, this means that tcount> t table, Ha is accepted and Ho is rejected and Ha1 is accepted. means that there is a positive and significant influence between Service Quality on Community Satisfaction at the Central Amuntai Sub-District Office of Hulu Sungai Utara Regency. To the Head of the Central Amuntai Sub-District of Hulu Sungai Utara Regency, and service officers in order to further improve the ability of employees, provide information and periodic socialization to the community.